Optimisme yang Tidak Menjanjikan: Kajian terhadap Transhumanisme dari Perspektif Antropologi Kristen: An Unpromising Optimism: Examining Transhumanism from a Christian Anthropological Perspective - Wendy; Alinurdin, David (Sekolah Tinggi Teologi SAAT, 2021)
Transhumanism is a cultural and philosophical movement that sees humans as having the right and morphological freedom to evolve towards a posthuman state by radically modifying and enhancing human nature and capacity using the latest technologies such as genetic engineering, robotics, artificial intelligence, and nanotechnology. The posthuman that transhumanism craves is the human condition impervious to degeneration, disease, and even death. The end goal is to live longer or even immortal to enjoy unlimited happiness. By observing the development of the transhumanist agenda, there are concerns from scholars in the interdisciplinary fields of science, technology, and theology that humanity will be transformed by technology or even become marginalized and extinct. This article aims to examine transhumanism from Christian anthropology, which includes three aspects: the origin and nature of man, the reality of human life, and solutions to human problems. The results of the study show that the promise of transhumanism regarding human evolution with morphological freedom and self-determination to strive for progress towards a posthuman state is unpromising to achieve because human nature, which has fallen into sin, tends to destroy or exchange good for evil. The agenda and optimism of transhumanism to completely remove degeneration, disease, and death from human life by using the latest technology is impossible to realize because all these realities are the impact of the fall of man into sin, which can only be overcome by divine means through redemptive work of Christ which carries out the transformation of soul and body holistically